The Use of Linktree as an Arabic Language Learning Innovation in the Digital Era - Nur Naria Dina Romadhon; Alifatun Nahla; Hamdan Nur Hidayat; Hadi Solikin (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2025)
Education in Indonesia continues to develop rapidly, utilizing modern technology and teaching methodologies to improve the quality and effectiveness of learning. This article explores the use of Linktree as an innovation in Arabic language learning. The main focus of this study is how Linktree is used by teachers to organize and present Arabic learning materials to make them more engaging and easier for elementary age students. This study uses the method of literature study and qualitative data analysis with the tutoring and Huberman model. The results of the study show that Linktree helps teachers manage various digital learning resources such as learning videos, interactive exercises, and e-modules in one integrated link. This increases accessibility, engagement, and active participation of students in learning. Despite constraints such as reliance on the internet network and limited features, Linktree has proven to be effective in supporting more interactive and efficient learning in. This research emphasizes the importance of strengthening digital literacy for teachers so that the use of simple technology such as Linktree can support the achievement of Arabic learning goals at the elementary level.